The influence of physical fitness on the symptoms of burnout - De Moraes, Mayra Grava [UNESP]; Calais, Sandra Leal [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP] (My University, 2019)
Studies point to a positive association of the regular practice of physical exercise and reducing burnout symptoms in several professions, being also able to decrease the risk of exhaustion; reduce levels of anxiety, stress and depression; improvement of mood; increasing physical wellbeing; improving work performance, physical, mental disposition and physical fitness. The objectives of this study were to compare levels of burnout and physical fitness between the male and female individuals, as well as to analyze and to associate the levels of physical aptitude between the groups that presented high and low risk for burnout. We evaluated 44 workers, consisting of physicians and teachers, being 21 females and 23 males. The results showed that female participants had higher scores on emotional exhaustion (23.9±10.8) compared to male participants (16.9±9.9). The individuals with high risk for burnout had a lower performance of cardiorespiratory fitness (33.55 ± 6.28 mL/kg/min) considered as “not recommended for health” when compared to individuals with low risk. A strong negative correlation was also observed between total burnout levels (r=-0.714, p=0.058) and VO2max and negative regular correlation (r=-0.446; p=0.256) between professional achievement (PA) and VO2max. We conclude that better cardiovascular fitness seems to be associated with decreased burnout symptoms and better ability to cope with occupational stress.
Keywords: Burnout and Physical Fitness; Physical Exercise